Visual evoked potentials to red-green stimulation in schoolchildren - POMPE, MANCA TEKAVČIČ; KRANJC, BRANKA STIRN; BRECELJ, JELKA (Visual neuroscience, 2006)
The aim is to study chromatic visual evoked potentials (VEP) to isoluminant red-green (R-G) stimulus in schoolchildren. Sixty children (7–19 years) with normal color vision were examined, 30 binocularly and 30 monocularly. The isoluminant point was determined for each child subjectively by using heterochromatic flicker photometry, and objectively from recordings. The stimulus was a 7° circle composed of horizontal sinusoidal gratings, with spatial frequency 2 cycles/degrees and 90% contrast, presented in onset-offset mode. VEP were recorded from Oz (mid-occipital) position. Age-dependent waveform changes and changes of the positive and negative wave were studied to both binocular and monocular R-G stimulation. Age-dependent waveform changes were observed to binocular and monocular R-G stimulation. In younger children the positive wave was prominent, whereas in older children also the negative wave became more evident. The latency of the positive wave decreased linearly with age to R-G binocular stimulation. To monocular stimulation no significant changes of the latency were observed. The amplitude of the positive wave dropped exponentially with age to binocular and monocular stimulation. The latency of the negative wave increased linearly with age to binocular and monocular stimulation, whereas the amplitude did not show age-dependent changes. These findings suggest that the chromatic VEP response undergoes evident age-dependent changes during the school-age period.